Efeito da introdução de bacias de detenção sobre a drenagem de águas pluviais: estudo de caso numa área urbana em Juiz de Fora, MG - Moreira, Leonardo Leon Leite (Universidade Federal de São Carlos, 2024)
The way urban development occurs in cities generally leads to major changes in the physical environment, such as increased demands on natural resources, environmental degradation, and alteration of the natural surface. With the process of urbanization, the surfaces of urban centers tend to become impervious, which alters the natural hydrological cycle of water. With the increase in surface runoff rates generated by this sealing, there is a need to implement more robust and complex stormwater management systems. Due to the recurrent flooding scenarios observed in recent years, discussions on urban drainage have become frequent, especially in developing countries such as Brazil. In these discussions, sustainable approaches to urban drainage have gained prominence, and much research has been conducted on their application. However, it is still clear that there are challenges to be overcome to better understand the use of more sustainable techniques that seek to restore, in some way, the natural water cycle. Given this scenario, this work aims to apply hydrological modeling in an area of recognized social vulnerability in the municipality of Juiz de Fora-MG, susceptible to recurrent flooding. Despite having an urbanized occupation, this area, far from the urban center of the municipality, has suffered few actions by public authorities, as happens in many vulnerable areas in Brazil. Using a predefined model, it is expected to simulate the application of detention basins in the area in question, as well as the application of more conventional techniques, to evaluate the impact generated on the local macrodrainage system. After carrying out the proposed simulations, it is expected to obtain, by way of comparison, a relationship between the implementation, maintenance, and operating costs of these approaches.
Effect of introducing detention basins on rainwater drainage: case study in an urban area in Juiz de Fora, MG
Keywords: Sistemas urbanos de drenagem sustentável; Sustainable urban drainage system; Bacias de detenção; Detention basins; Modelagem hidrológica; Hydrological modeling; Modelo de gerenciamento de águas pluviais; Stormwater management model; SWMM; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDRAULICA; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDROLOGIA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS